2013
DOI: 10.1108/ijlm-04-2012-0024
|View full text |Cite
|
Sign up to set email alerts
|

Reverse logistics: past research, current management issues, and future directions

Abstract: Purpose -The purpose of this paper is to identify the key issues faced by today's supply chain professionals when managing reverse logistics (RL) processes and compare these issues with the topics examined in extant research. By making such a comparison, the paper identifies areas of practical relevance that are being adequately addressed in the literature, as well as areas that may need further attention. Design/methodology/approach -The paper employed a Delphi method in order to uncover the most salient RL i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 87 publications
3
96
0
5
Order By: Relevance
“…Huscroft et al [26] confirm the significance of sustainability analysis in reverse supply chains. In this paper, we follow the approach of sustainability analysis in Choi and Chiu [25].…”
Section: Literature Reviewmentioning
confidence: 57%
“…Huscroft et al [26] confirm the significance of sustainability analysis in reverse supply chains. In this paper, we follow the approach of sustainability analysis in Choi and Chiu [25].…”
Section: Literature Reviewmentioning
confidence: 57%
“…They showed that combination of inventory and production making decision is frequently use in facility location and allocation cases. In another part they taxonomy 18 papers in different network structure respected to closed loop or reverse logistic activity in different layers (Huscroft, Hazen, Hall, Skipper & Hanna, 2013). They reach this conclusion just few papers concentrated on both closed-loop and forward logistic models comprehensively.…”
Section: Methods and Proceduresmentioning
confidence: 84%
“…The research method is presented, followed by an overview of the case study organisation. The company interview results and further implications for the Product stewardship Sarkis (1995), Lewis (2005), Ruskino (2007), Snir (2009), Rogers et al (2010) Green purchasing Tsoulfas and Pappis (2006), Gold et al (2009), Zhu et al (2007), Eltayeb and Zailani (2010), Green et al (2012), Yen and Yen (2012) Reverse logistics Lippman (2001), Blumberg (2005), Kleindorfer et al (2005), Varma et al (2005), Gupta (2005), Anderson and Skjoett-Larsen (2009), Jayant et al (2012), Huscroft et al (2013), Mutingi (2014) Recycle, reuse and remanufacturing Sarkis (1995), Kleindorfer et al (2005), Gupta (2005), Kuik et al (2011), Loomba and Nakashima (2012) Table 1 -Environmentally SSCM approaches and key references in the literature 'Environmental management' contains three different methods within a business strategy at different impact levels: reactive 'end of pipe' pollution control, proactive reusing, remanufacturing, and recycling of products and materials within the supply chain, and an integrated approach into value-seeking supply chain re-design integrated into business strategy (van Hoek, 1999). A value-seeking pollution preventive approach results in a better environmental performance than an end of pipe approach (Lee and Rhee, 2005).…”
Section: Introductionmentioning
confidence: 99%